L’ethnologie juridique au Collège de France : le cours de Jacques Flach sur les Institutions primitives (1892-1904) - Frédéric Audren (Clio@Themis)
This paper presents Jacques Flach’s Collège de France course in primitive law, which he taught from 1892 until 1904. It insists on the specificity of his historical and comparative approach. Ever attentive to studying institutions in their context, Flach proposes an innovative interpretation of feudalism, seeks to write a global history of law and endeavours to stress the institutional alterity of primitive societies. Flach is therefore among the first scholars to teach social and legal anthropology in France.